EFFICACY AND ROLE OF DYDROGESTERONE IN PREVENTING MISCARRIAGE: A SYSTEMATIC REVIEW AND META-ANALYSIS (Journal of Medical & Health Sciences Review, 2025)
Miscarriage and recurrent pregnancy loss (RPL) affects about 20% of all pregnancies in women causing clinical and emotional concerns. Health care practitioners commonly use dydrogesterone for the treatment of threatened miscarriage. Many studies have been conducted on the role and efficacy of dydrogesterone. Few studies support the role of dydrogesterone, however, other studies do not recommend dydrogesterone in preventing miscarriage, which necessitates a comprehensive review and meta-analyses on previously conducted randomized controlled trials. This meta-analyses not only cleared misconceptions regarding its use in threatened miscarriage, but also compared its role with other available options in progestogens. By evaluating all available data, its effectiveness has been concluded at the end which provides guidelines for health care practitioners helping them improve the treatment of patients.